PENINGKATAN PENGETAHUAN STUNTING BAGI ORANG TUA SERTA PEMANTAUAN PERTUMBUHAN PADA SISWA SEKOLAH ANAK HEBAT PAPUA - Elieser; Thimoty, James; Sari, Kurnia (LPPM Uncen, 2024)
Stunting or short stature is still one of the main nutritional problems among toddlers in Indonesia that has not been resolved. Children is stunted if the height is below -2 SD from the WHO standards. A total of 2.335 children in Jayapura City detected have stunting by the end of 2023. Besides social-economic problems and poor parental education, the practice of local culture in Papua also presents a challenge to resolving stunting. Therefore, the aim of this community service activity is to increase the knowledge and understanding of parents at the AHP (Great Children of Papua) School, Hamadi, Jayapura City regarding stunting using the parenting classes method. The number of participants was 48 people. Parenting classes activities were carried out in conjunction with growth monitoring activities to kindergarten and elementary school children at AHP schools, with a total of 64 students. From all community service activities through parenting classes carried out, it appears that the community has a better understanding of the meaning of stunting, the causes of stunting and the dangers of stunting on children's cognitive growth and development. Apart from that, from the results of monitoring growth in kindergarten and elementary school children based on TB/U, it was found that 10 children were stunted.